Problemy europejskiej cywilizacji a nowa humanistyczna antropologia = Problems of European civilization and new humanistic anthropology - Cynarski, Wojciech J. (Zielona Góra: Uniwersytet Zielonogórski)
The work is devoted fundamentally to the main problems of western civilization, Europe in particular. The analysis is based on a broad discourse concerning the problem. Among the main threats of the European civilization, the author mentions the rise of neopaganism in its various kinds, serious demographic problem resulting from moral crisis, threat of islamization and finally, involvement of education into ideology of egoism. The chance to survive can be seen in the return to Christian roots and ethos values, in education whose base will be new holistic anthropology perceiving Human in his rich spirituality and body, in the process of developing personality, and in the way of spiritual progress.
Keywords: antropologia; cywilizacja europejska; zagrożenia